Osmanlı-Safevî Mücadelesinde Ulemanın Rolü Kemal Paşazâde Örneği - Bulut, Halil İbrahim (Dinî araştırmalar, 2005)
This article aims to deal with the struggle between Ottomans and Safawids and the role of Ulema in this dispute. In order to control Anatolia, the Safawids propagate the shiite ideas among the people in there. On the other hand, Ottomans defended the Sunnî beliefs and took some the political and religious measures against the Qizilbash people. Thus aimed at gaining the help of Ulema. Kemal Paşazade, a longside with the other ulemas had set out to propagate anti-shiite ideas against the Qizilbash people. They wrote many books to prove that the Safawids were unbelievers therefore they remained outside the realm of Islam. Consequently, it is obligation on every Sunni believer to fight against them